Analysis of Consumer Value Perceptions on Purchasing Decisions for Environmentally Friendly Skincare Products - Djihadul Mubarok; Nashihatud Diniyah Jahro (Jurnal Mantik, 2026)
The background of this research focuses on the influence of consumer value perception on purchasing decisions for environmentally friendly skincare products in Indonesia. Amid the growing environmental awareness, consumers are increasingly considering the ecological impact of the products they purchase. Therefore, it is crucial to understand how consumer perceptions of product value influence purchasing decisions. The purpose of this study is to analyze the impact of consumer value perception, which includes functional value, emotional value, price value, and social value, on purchasing decisions for environmentally friendly skincare products in Indonesia. The research employs a quantitative approach, with data collected through a questionnaire distributed to 150 respondents. The data were analyzed using multiple linear regression with SPSS software, along with validity, reliability, and classical assumption tests. The results indicate that functional value, emotional value, and price value significantly influence purchasing decisions, while social value does not have a significant effect. The coefficient of determination (R²) is 0.539, meaning that 53.9% of the variation in purchasing decisions can be explained by these four variables. In conclusion, marketing strategies for environmentally friendly skincare products in Indonesia should emphasize tangible benefits, emotional experiences, and competitive pricing, while social value does not play a significant role in purchasing decisions